Endosperm-based incompatibilities in hybrid monkeyflowers. Issue 7 (25th April 2021) - Kinser, Taliesin J.; Smith, Ronald D.; Lawrence, Amelia H.; Cooley, Arielle M.; Vallejo-Marín, Mario; Conradi Smith, Gregory D.; Puzey, Joshua R.
Abstract: Endosperm is an angiosperm innovation central to their reproduction whose development, and thus seed viability, is controlled by genomic imprinting, where expression from certain genes is parent-specific. Unsuccessful imprinting has been linked to failed inter-specific and inter-ploidy hybridization. Despite their importance in plant speciation, the underlying mechanisms behind these endosperm-based barriers remain poorly understood. Here, we describe one such barrier between diploid Mimulus guttatus and tetraploid Mimulus luteus . The two parents differ in endosperm DNA methylation, expression dynamics, and imprinted genes. Hybrid seeds suffer from underdeveloped endosperm, reducing viability, or arrested endosperm and seed abortion when M. guttatus or M. luteus is seed parent, respectively, and transgressive methylation and expression patterns emerge. The two inherited M. luteus subgenomes, genetically distinct but epigenetically similar, are expressionally dominant over the M. guttatus genome in hybrid embryos and especially their endosperm, where paternal imprints are perturbed. In aborted seeds, de novo methylation is inhibited, potentially owing to incompatible paternal instructions of imbalanced dosage from M. guttatus imprints. We suggest that diverged epigenetic/regulatory landscapes between parental genomes induce epigenetic repatterning and global shifts in expression, which, in endosperm, may uniquely facilitate incompatible interactions between divergent imprinting schemes, potentially driving rapid barriers. Abstract : Diverged epigenetic/regulatory landscapes between parental genomes result in epigenetic repatterning in hybrids that drive global shifts in endosperm gene expression patterns.